2018
DOI: 10.1507/endocrj.ej16-0387
|View full text |Cite
|
Sign up to set email alerts
|

Usage of continuous glucose monitoring (CGM) for detecting an unrecognized hypoglycemia and management of glucocorticoid replacement therapy in adult patients with central hypoadrenalism

Abstract: Patients with adrenal insufficiency require appropriate glucocorticoid replacement therapy; however, reliable biological parameters for optimizing glucocorticoid supplementation are limited. The physician has to rely primarily on clinical judgment, carefully taking into account signs and symptoms potentially suggestive of over- or under-replacement. We have found that some patients who are viewed as receiving sufficient doses of glucocorticoids occasionally exhibit morning headache or morning discomfort, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
(63 reference statements)
0
6
0
1
Order By: Relevance
“…A previous research has investigated cortisol dose adjustment using continuous glucose monitoring in patients with secondary hypoadrenalism [ 11 ]. CAH with 17α-hydroxylase deficiency leads to adrenal insufficiency; however, incomplete cortisol deficiency was the distinguishing feature of our patient.…”
Section: Discussionmentioning
confidence: 99%
“…A previous research has investigated cortisol dose adjustment using continuous glucose monitoring in patients with secondary hypoadrenalism [ 11 ]. CAH with 17α-hydroxylase deficiency leads to adrenal insufficiency; however, incomplete cortisol deficiency was the distinguishing feature of our patient.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Nevertheless, a recent study using a continuous glucose monitoring system reported a number of cases of nocturnal hypoglycemia in adult patients with adrenal insufficiency despite glucocorticoid replacement. [12][13][14] In Islamic culture, patients with adrenal insufficiency can suffer from hypoglycemia during Ramadan fasting, despite the continuance of glucocorticoid replacement therapy. 15 These reports indicate adrenalinsufficient adults are also prone to hypoglycemia, especially during fasting, and that the frequency may have been underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoglycaemia is considered a rare problem for adults with adrenal insufficiency (AI) 52 . However, in those with morning headache or discomfort, overnight CGM revealed hypoglycaemia in 5 out of 6 patients who had all demonstrated normal morning fingerprick glucose testing 53 . Increasing hydrocortisone dosing not only prevented overnight hypoglycaemia but also resulted in resolution of symptoms 53 .…”
Section: Adrenal Insufficiencymentioning
confidence: 92%